Cost-Effectiveness of Zoledronic Acid Versus Oral Alendronate for Postmenopausal Osteoporotic Women in China - You, Ruxu; Zhang, Yu; Wu, David Bin-Chia; Liu, Jinyu; Qian, Xinyu; Luo, Nan; Mori, Takahiro (Frontiers in Pharmacology, 2020)
Objective: This study aims to estimate the cost-effectiveness of yearly intravenous zoledronic acid treatment versus weekly oral alendronate for postmenopausal osteoporotic women in China. Methods: We used a markov microsimulation model to compare the cost-effectiveness of zoledronic acid with alendronate in Chinese postmenopausal osteoporotic women with no fracture history at various ages of therapy initiation from health care payer perspective. Results: The incremental cost-effectiveness ratios (ICERs) for the zoledronic acid versus alendronate were $23581/QALY at age 65 years, $17367/QALY at age 70 years, $14714/QALY at age 75 years, and $12169/QALY at age 80 years, respectively. In deterministic sensitivity analyses, the study demonstrated that the two most impactful parameters were the annual cost of zoledronic acid and the relative risk of hip fracture with zoledronic acid. In probabilistic sensitivity analyses, the probabilities of zoledronic acid being cost-effective compared with alendronate were 70-100% at a willingness-to-pay of $29340 per QALY. Conclusions: Among postmenopausal osteoporotic women in China, zoledronic acid therapy is cost-effective at all ages examined at a willingness-to-pay from health care payer perspective, compared with weekly oral alendronate. In addition, alendronate treatment is shown to be dominant for patients at ages 65 and 70 with full persistence. This study will help clinicians and policymakers make better decisions about the relative economic value of osteoporosis treatments in China.